Pengaruh Model Pembelajaran Discovery Learning dengan Problem Based Learning (PBL) Terhadap Hasil Belajar ditinjau dari Keaktifan Siswa - Astri Retnaningsih; Acep Kusdiwelirawan; Imas Ratna Ermawati (Universitas Muhammadiyah Purworejo, 2019)
This study aims to find the Effect of Discovery Learning with Problem Based Learning to Result of Study in terms of Student Activity. The method used in this study is the True Experimental Design method. Based on the results of hypothesis testing using Two Path ANAVA, the first hypothesis obtained a value of Fhitung= 12.56 > Ft(α=0.05)= 4.06 ; Ft(α=0.01)= 7.24, while for the second hypothesis Fhitung=26.40 > Ft(α=0.05) = 4.06 ; Ft(α=0.01) = 7.24. Then for the third and fourth hypotheses can be calculated using the t-Dunnet test, the value thitung= 9.05 > tt(α=0.05)= 1.678 ; tt(α=0.01)= 2.411 and thitung= 5.64 > tt(α=0.05)= 1.678 ; tt(α=0.01)= 2.411. So from the results of this study it can be concluded that there is an Effect of Discovery Learning with Problem Based Learning to Result of Study in terms of Student Activity.